Georges Pletho Gemistus: Reforming Byzantium at the edge of the cliff: A short introduction to Pletho’s political thinking - Christias, Panagiotis (Dia-noesis: A Journal of Philosophy, 2024)
Pletho’s turn to the ancient Gods and Plato signifies actually a turn to the future of the national State. A well-defended country is a well-organized one. In order to be well-organized, the government and administration should be founded on the general national interest, for only national ideology brings the necessary stability and moral force to the long battle for Greek national survival. No wonder that scholars such as Sathas and Zakythinos consider him to be the first of the moderns, putting in the centre of his universe his mystical ideal of στρατιῶται (soldiers).